Abscisic acid-deficient sit tomato mutant responses to cadmium-induced stress - Pompeu, Georgia B.; Vilhena, Milca B.; Gratï¿½o, Priscila L. [UNESP]; Carvalho, Rogï¿½rio F. [UNESP]; Rossi, Mï¿½nica L.; Martinelli, Adriana P.; Azevedo, Ricardo A. (Springer Nature, 2017)
There is a very effective cross-talk between signals triggered by reactive oxygen species and hormonal responses in plants, activating proteins/enzymes likely to be involved in stress tolerance. Abscisic acid (ABA) is known as a stress hormone that takes part in the integration of signals. This work aimed to characterize the biochemical response and ultrastructural changes induced by cadmium (Cd) in the Micro-Tom (MT) sitiens ABA-deficient mutant (sit) and its wild-type (MT) counterpart. MT and sit plants were grown over a 96-h period in the presence of Cd (0, 10, and 100ï¿½μM CdCl2). The overall results indicated increases in lipid peroxidation, hydrogen peroxide content and in the activities of the key antioxidant enzymes such as catalase, glutathione reductase, and ascorbate peroxidase in both genotypes. On the other hand, no alteration was observed in chlorophyll content, while the activity of another antioxidant enzyme, superoxide dismutase, remained constant or even decreased in the presence of Cd. Roots and shoots of the sit mutant and MT were analyzed by light and transmission electron microscopy in order to characterize the structural changes caused by the exposure to this metal. Cd caused a decrease in intercellular spaces in shoots and a decrease in cell size in roots of both genotypes. In leaves, Cd affected organelle shape and internal organization of the thylakoid membranes, whereas noticeable increase in the number of mitochondria and vacuoles in MT and sit roots were observed. These results add new information that should help unravel the relative importance of ABA in regulating the cell responses to stressful conditions induced by Cd apart from providing the first characterization of this mutant to oxidative stress.
Keywords: Oxidative stress; Phytohormones; Reactive oxygen species; Root and leaf anatomy; Solanum lycopersicum; Ultrastructure